Action of toxin Hl3 on skeletal muscle - Escobar, Enrique (2003)
Hl3 is a toxin isolated by our investigation group from Hadruroides lunatus scorpion venom by ionexchange chromatography on CM-Sephadex C-25 to pH 7, and which produce contraction and paralysis in the inoculated limb of white mice. In this work we have determined that inoculation of Hl3 (26 μg) in gastrocnemius muscle from mice produces the release in plasma of creatine kinase and lactate deshidrogenase. The creatine kinase activity increases from 210 UI/L to 8015 UI/L in 60 minutes, whrereas the LDH activity increases from 174 UI/L to 1697 UI/L in 90 minutes. By PAGE-SDS it, was demonstrated that incubation of Hl3 with gastrocnemius muscle isolated from white mice, in physiological solution to pH 7, produces the release of other different muscular proteins as well. In addition Hl3 can increase the calcium intramuscular 3,5 fold, after 45 minutes of action. Our results suggest that Hl3 has specific action on the muscle, affecting the sarcolema permeability and producing the release of muscle proteins. In addition the increase of calcium could produce hipercontraction and destruction of muscular fibers.